Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMA dalam Menyelesaikan Soal Berkonteks Budaya Melayu Kepulauan Riau - Wulan, Roro; Febrian, Febrian; Rahmatina, Desi (Universitas Maritim Raja Ali Haji, 2025)
Existing studies show that problem-solving is still a problematic learning outcome faced by grade XI students at SMA Negeri 1 Bintan Timur. This study aims to describe the mathematical problem-solving ability of high school students in the context of the Malay culture of the Riau Islands. The type of research applied is descriptive qualitative. The source of information for this study came from students of class XI E at SMA Negeri 1 Bintan Timur. The data collection methods applied consisted of tests, interviews, and documentation. The data analysis process in this study included data reduction, data presentation, and conclusion. The results of this study indicate that there are 2 students with a percentage of 7% in the high category, 9 students with a rate of 33% in the medium category, and 16 students with a percentage of 60% in the low category. Integrating Malay culture in mathematics research can help students understand mathematics in everyday life and enrich their understanding. In addition, students learn theory and see the real application of mathematics in their daily lives.